The effects of co-movement, macroeconomic announcement dates and major events on foreign exchange: the case of the Australian dollar and other selected currencies - Haw, Hui Mun (2018)
This paper investigates on the co-movement of the Australian Dollar (AUD) with the Euro (EUR), Pound (GBP), Yen (JPY) and New Zealand Dollar (NZD), the effects of macroeconomic announcement date on the AUD’s return and volatility, and also the effects of major events, namely the Brexit and 2016 U.S presidential election on the return and volatility of the currencies mentioned. All currencies selected are paired up with the USD and are termed as AUD/USD, EUR/USD, GBP/USD, JPY/USD and NZD/USD.